The Incidence Rate, Risk Factors and Clinical Outcome of Acute Kidney Injury in Critical Patients - Susan MOHAMMADI KEBAR; Saeed HOSSEINI NIA; Nasrollah MALEKI; Afshan SHARGHI; Arash SHESHGELANI (Tehran University of Medical Sciences, 2018)
Background: Acute kidney injury (AKI) is the most common cause of organ dysfunction in intensive care unit (ICU) patients. There is no consensus definition of AKI in ICU patients. Therefore, we aimed to evaluate the incidence rate, risk factors and clinical outcome of AKI using the RIFLE (Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease) classification in ICU patients. Methods: We performed a retrospective cohort study, on 900 patients admitted to the ICU during a one year period at Imam Khomeini Hospital in Ardebil, Iran from 2014 to 2015. AKI was defined by the consensus RIFLE criteria. Results: The overall incidence rate of AKI was 37%. The patients with AKI were also classified according to RIFLE as follows: Risk (8.2%), Injury (13.4%), Failure (13.2%), Loss of kidney function (1.3%), and End-stage kidney disease (0.8%). The mortality rate was 58.3% for AKI patients, and 13.4% for non-AKI patients (P<0.001). Patients in RIFLE-R (Risk) had a mortality rate of 37.8% compared with 48.8% for those in RIFLE-I (Injury) and 76.5% for RIFLE-F (Failure) patients (P<0.0001). Significant risk factors to the development of AKI were included: age more than 60 yr, increased length of hospital stay, systolic blood pressure less than 100 mm Hg, requirement of mechanical ventilation, relevant comorbidities, anemia, thrombocytopenia, increased serum bilirubin and liver enzymes, and serum sodium abnormalities. Conclusion: The RIFLE classification is a useful and suitable clinical tool to evaluate the incidence and mortality rate of AKI. In ICU patients, AKI is associated with increased mortality rate.